2009
DOI: 10.1016/j.jad.2008.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Decreased muscarinic receptor binding in the frontal cortex of bipolar disorder and major depressive disorder subjects

Abstract: Background-Dysfunction of the cholinergic muscarinic receptors has been implicated in the pathology of bipolar disorder and major depressive disorder. However, there is conflicting evidence regarding the association between individual muscarinic receptors and the two disorders.Methods-We used the muscarinic receptor selective radioligands [ 3 H]pirenzepine, [ 3 H] AFDX-384 and [ 3 H]4-DAMP to measure the levels of muscarinic 1 (CHRM1) and muscarinic 4 (CHRM4) receptors, muscarinic 2 (CHRM2) and muscarinic 4 (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 52 publications
7
70
1
Order By: Relevance
“…Although here we did not examine the receptor subtype involved in the Oxo anxiolytic effect, several reports may give suggestions on antidepressant role of M1 receptor, which has been found throughout the brain with the highest concentrations in cerebral cortex and hippocampus (Hohmann et al 1995;Levey et al 1995). Previous works have shown that disturbances in the cholinergic activity may be associated to neurobiology of depression (Janowsky et al 1972), and muscarinic receptors have been found downregulated in the prefrontal cortex of depressed patients (Gibbons et al 2009), or upregulated in the hippocampus following mood stabilizers like lithium treatment (Marinho et al 1998). Recent studies have identified an activity-dependent long-term depression in deep layers of the rat medial prefrontal cortex mediated by the M1 receptor, which may be relevant for neurological disorders (Caruana et al 2011).…”
Section: Machr Subtypes Mediating Anxiolytic Effects Of Oxomentioning
confidence: 81%
“…Although here we did not examine the receptor subtype involved in the Oxo anxiolytic effect, several reports may give suggestions on antidepressant role of M1 receptor, which has been found throughout the brain with the highest concentrations in cerebral cortex and hippocampus (Hohmann et al 1995;Levey et al 1995). Previous works have shown that disturbances in the cholinergic activity may be associated to neurobiology of depression (Janowsky et al 1972), and muscarinic receptors have been found downregulated in the prefrontal cortex of depressed patients (Gibbons et al 2009), or upregulated in the hippocampus following mood stabilizers like lithium treatment (Marinho et al 1998). Recent studies have identified an activity-dependent long-term depression in deep layers of the rat medial prefrontal cortex mediated by the M1 receptor, which may be relevant for neurological disorders (Caruana et al 2011).…”
Section: Machr Subtypes Mediating Anxiolytic Effects Of Oxomentioning
confidence: 81%
“…Using radiolabels for M 1 -M 4 , Gibbons et al (2009) evaluated receptor density changes in the postmortem frontal cortex of patients with MDD or bipolar disorder (BD). Both M 2 and M 3 binding sites were downregulated in MDD but only M 2 in BD.…”
Section: Discussionmentioning
confidence: 99%
“…More integrative approaches, determining expression at the levels of radioligand binding, mRNA, and protein, lead to the discovery that in the cortex the reduced binding density was due to lower levels of the M1 receptor [44], while in the hippocampus it was the M4 receptor that was expressed at a lower level [45]. Of particular note are the findings that in psychiatric disorders: (1) the decrease in the M1 receptor is specific to schizophrenia [42,46] and (2) changes in M2 and M3 receptors appear to be limited to subcortical regions [47,48].…”
Section: Muscarinic Receptors and Schizophreniamentioning
confidence: 99%